De tocaia na infância: uma análise da proposta pedagógica da escola Toca do Futuro - Janei Neto, Vitor (2017)
The present dissertation work aims to analyze aspects of the pedagogical proposal of the Toca do Futuro, school of application of the Toca Institute. Toca Institute is a non-profit organization that develops actions and research focused on sustainability education. The headquarters of the Toca Institute and the Toca do Futuro school are located at Fazenda da Toca, a rural property that produces organic food, located in the city of Itirapina, in the interior of the State of São Paulo. As a methodological strategy, we analyze some topics of the pedagogical proposal, as a way of delineating the modes of subjectivation that this school intends to engender. By subjectivation modes are understood the subjectivities, the ways of being, the lifestyles, the forms of existence that are produced from discourses, statements, laws, norms, institutions and practices, linked to the relations of knowledge and power that They cross bodies. Among the main theoretical references used in the research are the studies of Nietzsche, Spinoza, Michel Foucault, Gilles Deleuze and Felix Guattari.